Cavity enhanced absorption spectroscopy measurements of pressure-induced broadening and shift coefficients in the upsilon (1)+upsilon (3) combination band of ammonia - Bell, C; Dhib, M; Hancock, G; Ritchie, G; Helden, J; Leeuwen, N (2009)
Cavity enhanced absorption spectroscopy is performed using an external cavity diode laser operating around 1516 nm. We demonstrate a sensitivity of 6×10-8 cm-1∈Hz-1/2 and utilise a simple method to measure pressure-induced broadening and shift coefficients. The broadening and shift coefficients for six gases (helium, neon, argon, xenon, oxygen and nitrogen) have been determined at room temperature for four transitions in the υ 1+υ 3 combination band of ammonia. Comparisons of the broadening coefficients with previous work in this region, where it exists, show good agreement. The broadening and shift coefficients of nitrogen and oxygen are also in good agreement with calculated values using the Robert and Bonamy theory. Both the broadening and shift coefficients show a clear trend through the rare gases, which can be explained in terms of the varying magnitude of the long range attractive forces operating between the colliding partners. We also demonstrate the application of the Parmenter-Seaver formalism to estimate the potential well depth of the ammonia dimer from the obtained broadening coefficients. The obtained well depth agrees well with theoretical calculations. © 2008 Springer-Verlag.